Det næstekærlige fællesskab: Bemærkninger til kristendommens selv-dekonstruktion - Lysemose, Kasper (Religionsvidenskabeligt tidsskrift, 2017)
The paper presents the self-deconstruction of Christianity in the guise of two claims: i. The God withdrawn is part in a community of those who are abandoned by God - namely as the with' of their being-with. ii. Christian love is the reserve in Christianity that exposes us to this very being-with - i.e. to something in Christianity older than Christianity itself. Jean-Luc Nancy's general ontology of being-with and its specific configuration as a deconstruction of Christianity' is introduced. Subsequently this deconstruction is traced in The Works of Love by Søren Kierkegaard.